Efficiency and cost estimation for a static frequency converter and a rail power conditioner based on an indirect modular multilevel converter in railways applications - Tanta, Mohamed (2017)
This paper presents a comparative study between two different power electronics solutions for electrified railway substations to overcome some drawbacks which could appear on the public grid side. These drawbacks or troubles on the public grid side are mainly the harmonics and the negative sequence components (NSCs) of currents, which could become clear in the case of feeding single-phase locomotives or unbalanced loads. The static frequency converters (SFCs) and the rail power conditioners (RPCs) based on an indirect AC/DC/AC modular multilevel converter (MMC) are the main area of interest in this study, taking into consideration the costs estimation analysis between solutions, the efficiency and the power quality on the public grid side. Both systems of SFC and RPC based on an indirect MMC operate on medium voltage levels to feed the catenary line and to solve the problems of harmonics and NSCs. Along the paper are described the system architecture, the control algorithm, the inherent benefits, the estimated cost of implementation, and the operation efficiency based on computational simulation results for each system.